2013
DOI: 10.1257/app.5.1.163
|View full text |Cite
|
Sign up to set email alerts
|

Savings Constraints and Microenterprise Development: Evidence from a Field Experiment in Kenya

Abstract: To what extent does the lack of access to formal …nancial services impede business growth in low-income countries? While most research on this issue has so far focused on credit market failures, this paper focuses on the role of access to formal saving services. We conducted a …eld experiment in which a randomly selected sample of self-employed individuals in rural Kenya got access to an interest-free bank account. As the bank charged substantial withdrawal fees, the de facto interest rate on the account was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
479
1
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 636 publications
(551 citation statements)
references
References 36 publications
31
479
1
4
Order By: Relevance
“…Por ejemplo, Karlan, Lakshmi y Zinman (2014) describen una barrera que restringe el acceso: los altos costos de transacción. Frente a los bajos y erráticos montos de ahorro que mantienen dichas poblaciones, los costos de entrada y de operación de estas entidades financieras son altos y ello desincentiva la presencia en algunas localidades (Dupas y Robinson, 2013). A este respecto, no es casual que en algunos países se hayan introducido medidas legislativas conducentes a obligar a los bancos comerciales a crear cuentas básicas que tienen como características esenciales que no se cobra por la apertura de la cuenta ni tampoco por el número de transacciones, pero tienen un tope respecto del saldo que se mantiene.…”
Section: Una Revisión De La Literaturaunclassified
“…Por ejemplo, Karlan, Lakshmi y Zinman (2014) describen una barrera que restringe el acceso: los altos costos de transacción. Frente a los bajos y erráticos montos de ahorro que mantienen dichas poblaciones, los costos de entrada y de operación de estas entidades financieras son altos y ello desincentiva la presencia en algunas localidades (Dupas y Robinson, 2013). A este respecto, no es casual que en algunos países se hayan introducido medidas legislativas conducentes a obligar a los bancos comerciales a crear cuentas básicas que tienen como características esenciales que no se cobra por la apertura de la cuenta ni tampoco por el número de transacciones, pero tienen un tope respecto del saldo que se mantiene.…”
Section: Una Revisión De La Literaturaunclassified
“…The two closest papers conducted in East Africa are Dupas and Robinson (2013a) in which only 35% of people ever used the account, and Dupas, Keats and Robinson (2015) in which only 28% did. As here, the people who used the accounts saved fairly large sums, however, and so the positive treatment effects were driven by a minority of users who benefited greatly.…”
Section: Comparison With Other Savings Studiesmentioning
confidence: 99%
“…Consequently, many studies simply do not ask about home savings (i.e. Dupas and Robinson 2013a). In this study, however, we extensively pre-tested modules aimed in part to measure home savings.…”
Section: Introductionmentioning
confidence: 99%
“…It could also be that stakeholders have biased perceptions of environmental issues. Indeed, while our proposed priorities for the environment typically focus on the long-term outlook, some recent studies, including Dupas [24], have shown that households in Africa tend to exhibit present-biased preferences. As a result, local stakeholders may be tempted to under-invest in long-term assets such as the environment.…”
Section: Expert and Stakeholder Views Related To Priorities Per Sectorsmentioning
confidence: 99%